You Cannot Shift an Old Tree Without it Dying—Home Swapping as a Suitable Strategy for Older Downsizers? - Kitzmann, Robert (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
The current global trend of increasing per capita living space in combination with more and smaller households will intensify resource and energy consumptions in the housing sector. Scientific scholars, thus, unanimously plead for a reduction of per capita living consumption. Since the demographic trend of aging will further contribute to a high increase of single households and cause further under-occupation of living space, the potential to spatially downsize is particularly high among those older age cohorts. However, the often-limited housing choices for seniors do not allow for a large-scale downsizing development. Beyond that, the discourse on housing downsizing lacks a discussion of distinct strategies of how to effectively offer options for older people to do so. Hence, the paper at hand presents the distinct instrument of home swapping which has lately been introduced by several German municipalities to more adequately allocate the existing housing space. Since a profound scientific debate of this approach is still pending, this contribution discusses home swapping as a suitable strategy to incentivize older households to downsize on their living space. In order to do so, the home swapping schemes of four German cities have been analyzed to add scientific evidence on the potentials and challenges of the instrument to downsize housing consumption